FRAMING OF @YOURFAVORITEGUY’S TIKTOK VIDEOS ON THE PALESTINE GENOCIDE - Ahmad, Aresa; Suhaimi, Che Sarah Raihana; Mohd Wahama, Siti Aisyah; Razali, Khairil Azwar (Kulliyyah of Sustainable Tourism and Contemporary Languages (KSTCL), 2025)
The study aims to examine and analyse the framing techniques employed by the TikTok influencer @YourFavoriteGuy in 100 videos related to Palestine. The objective is to understand how this influencer shapes and communicates narratives about the Palestinian cause. To achieve this, 100 videos were randomly selected from the influencer’s TikTok page. The selection criteria focused on videos related to Palestine, posted between October 7th, 2021, and May 2024. The analysis applied the message frames adopted by Xiong et al. (2019). These frames categorize the content into five distinct themes: direct political content, call to action, reference to victims, mentioning the role of activists, and challenges or other artistic expressions. The study’s findings reveal that the most prominent frame in the videos is direct political content, indicating a strong focus on political aspects of the Palestinian cause. Conversely, the least prominent frame is challenges and other artistic expressions, suggesting that these types of content are less frequently used by the influencer concerning the Palestinian narrative.